Influence of Oxidants on the Stability of Tocopherol in Model Nanoemulsions: Role of Interfacial Membrane Organized by Nonionic Emulsifiers - Jinhyuk Kim; Ha Youn Song; Seung Jun Choi (Journal of Chemistry)
Nanoemulsions were prepared by using emulsifiers with various sizes of hydrophilic and hydrophobic groups to determine the impact of interfacial characteristics on the stability of α-tocopherol incorporated into the nanoemulsions. The α-tocopherol concentration remaining after 3 weeks of storage at 25°C depended greatly on the type of oxidative stress, which indicated that the environment surrounding the oil droplets could determine the stability of α-tocopherol in nanoemulsions. α-Tocopherol was gradually degraded by radical-mediated oxidation over storage, and approximately 60% of its initial concentration remained after 3 weeks of storage. However, under acid- and iron-mediated oxidation, α-tocopherol concentration steeply decreases for the initial 3-day storage, but the degradation rate of α-tocopherol decreased after 3 days of storage and over 90% of the initial α-tocopherol remained after 3 weeks of storage. Interestingly, and contrary to our expectations, the thickness and/or density of the droplet interfacial membrane rarely affected the stability of α-tocopherol incorporated into nanoemulsions. Although it is difficult to generalize beyond α-tocopherol, we conclude that the properties of oil droplet surfaces had no influence on the storage stability of α-tocopherol encapsulated in the droplets.